From Transit To Home: The Impact Of Transit-Oriented Development (TOD) On Residential Intentions In Tod-Based Areas - Mahaputra, Gema Patria (Syntax Corporation, 2025)
Transit-Oriented Development (TOD)-based residential areas have emerged as a solution to address urbanization and mobility challenges in metropolitan regions. This concept offers housing with easy access to public transportation and various supporting facilities. However, despite its numerous benefits, public adoption of the TOD concept remains varied. This study aims to identify key factors within the TOD framework that influence individuals' intention to reside in TOD-based areas. Using a quantitative approach and Partial Least Squares-Structural Equation Modeling (PLS-SEM), data were collected from potential residents interested in purchasing properties within TOD projects connected to Jabodebek LRT and KRL networks. The results indicate that conducive and seamless pedestrian environment, affordability and quality of the public transport system, pedestrian amenities, and compact and mixed-development concept all have a significant influence on individuals’ intention to reside in TOD areas. The implications of this study provide a valuable foundation for developers in designing more attractive and context-responsive TOD communities that align with the needs and preferences of urban populations.